Fumigant and Non-Fumigant Nematicides Labeled for Agronomic Crops in Florida - Zane Grabau (EDIS)
Plant-parasitic nematodes can cause severe yield loss of agronomic crops in Florida. Chemical products for managing plant-parasitic nematodes are called nematicides. This three-page facts heet describes the nematicides registered for use in Florida. Written by Zane Grabau and published by the Department of Entomology and Nematology.http://edis.ifas.ufl.edu/in1152